1993
DOI: 10.1007/bf02179832
|View full text |Cite
|
Sign up to set email alerts
|

Die Bedeutung von Gingivaduplikaturen beim orthodontischen Lückenschluß

Abstract: 23 extraction sites from group I (14 patients, average age 25 years, two months) which exhibited gingival invagination during orthodontic space closure with fixed appliances were compared with an equal number of extraction sites without gingival invaginations from group II patients (13 patients, average age 22 years, three months). Clinical analysis criteria were: interdental distance, treatment period, depth of gingival invagination, plaque index, gingival index, and probing depth. The marginal bone level at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 12 publications
1
13
0
12
Order By: Relevance
“…Explanations regarding the development of gingival ingrowths include increased proliferation of connective tissue and epithelium, to a change in bone topography and/or morphology, and the impaired development of free gingival and transseptal fibers, or to a bone fracture while the teeth were being extracted [9,11,15,16]. As a consequence, there can be increased marginal bone loss in the spaces between neighboring teeth, a reduction in interdental bone height, and increased time necessary for the orthodontic space to close [16]. It sometimes becomes impossible to close the remaining spaces completely due to pronounced gingival invagination [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Explanations regarding the development of gingival ingrowths include increased proliferation of connective tissue and epithelium, to a change in bone topography and/or morphology, and the impaired development of free gingival and transseptal fibers, or to a bone fracture while the teeth were being extracted [9,11,15,16]. As a consequence, there can be increased marginal bone loss in the spaces between neighboring teeth, a reduction in interdental bone height, and increased time necessary for the orthodontic space to close [16]. It sometimes becomes impossible to close the remaining spaces completely due to pronounced gingival invagination [7].…”
Section: Introductionmentioning
confidence: 99%
“…Erklärungen zur Entstehung reichen von vermehrter bindegewebiger und epithelialer Proliferation, über eine Veränderung der Knochentopographie/-morphologie, bis hin zur Beeinträchtigung der Ausbildung freier gingivaler und transseptaler Fasern oder Fraktur von Knochen bei der Extraktion der Zähne [9,11,15,16]. In der Folge kann es zu einem vermehrten marginalen Knochenverlust an den die Lücken begrenzenden Zähnen, zu einer Reduktion der interdentalen Knochenhöhe und zu einem erhöhten Zeitaufwand beim orthodontischen Lückenschluss kommen [16]. In einigen Fällen ist es auf Grund der Ausprägung sogar nicht mehr möglich, die Restlü-cken vollständig zu schließen [7].…”
Section: Introductionunclassified
“…Wehrbein et al [34] performed a clinical radiological study in which they showed that gingival invagination can hinder orthodontic space closure. Due to tissue hyperplasia, space closure is often inadequate and may take more time.…”
Section: Intermediate To Long-term Consequences Of Gingival Invaginationmentioning
confidence: 99%
“…About 35% of all extraction cases are at risk of developing gingival invaginations [78]. Explanations how invaginations develop range from increased connective tissue and epithelial proliferation, to a change in bone topography and bone morphology, impaired formation of free gingival and transseptal fibers, and bone fracture during tooth extraction [77,80,97]. Consequently, there can be increased marginal bone loss in the spaces of adjacent teeth, a loss in interdental bone height, and additional time necessary for orthodontic space closure [97].…”
Section: Gingival Invaginationsmentioning
confidence: 99%
“…Erklärungen zur Genese reichen von vermehrter bindegewebiger und epithelialer Proliferation, über eine Verände-rung der Knochentopographie/-morphologie, bis hin zur Beeinträchtigung der Ausbildung freier gingivaler und transseptaler Fasern oder die Fraktur von Knochen bei der Extraktion der Zähne [77,80,97]. In der Folge kann es zu einem vermehrten marginalen Knochenverlust an den Lücken begrenzenden Zähnen, einer Reduktion der interdentalen Knochenhöhe sowie einem erhöhten Zeitaufwand beim orthodontischen Lückenschluss kommen [97]. Der langfristige Einfluss auf die parodontale Gesundheit in diesen Bereichen ist nur unzureichend dokumentiert.…”
Section: Gingivaduplikaturenunclassified